PENGARUH PERCEIVED ORGANIZATIONAL CULTURE TERHADAP COUNTERPRODUCTIVE WORK BEHAVIOR DENGAN ROLE INDIVIDUAL PERSONALITY NARCISSISM SEBAGAI VARIABEL MODERASI DI MASA PANDEMI COVID-19 - Monica Sandra; Suharnomo Suharnomo (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of perceived organizational culture on counterproductive work behavior with the role of narcissistic individual personality as a moderating variable. This study uses the perception of organizational culture as an independent variable, counterproductive work behavior as the dependent variable, and the role of individual personality as a moderating variable. The population in this study were all active employees of Bank Jateng Main Branch Office, amounting to 90 people. This study takes the entire population as a sample or is called a census. Data obtained from questionnaires were processed and analyzed using SPSS and SmartPLS programs. The results showed that the perception of organizational culture had a negative and significant effect on counterproductive work behavior. While the results of the moderating variable, namely the role of the individual personality of narcissism, managed to become a moderating variable between perceptions of organizational culture and counterproductive work behavior.